Constructing Roma students as ethnic 'others' through orientalist discourses in Bulgarian schools. Issue 1 (2nd January 2018) - Lambrev, Veselina; Traykov, Bozhin; Kirova, Anna
Abstract: This article uses the case of Bulgarian, predominantly Roma, schools to illustrate the long history of stereotypes about Roma people dating back to modernity's discursive binary oppositions of 'civilized' vs. 'barbarians.' The data from a longitudinal study with 12 Bulgarian educators showed the modes by which Roma as the Other is created in the school context as a universal cognitive category, internalized in social and individual identities that divide the world into 'us' and 'them.' The paper argues that Bulgarian teachers' perceptions of attitudes, behavior, and values of Roma communities are, in fact, a projection of the discursive representations with which western European modernity has constructed the Balkan region. This research contributes to further explicating how the ideological paradigm of neoliberalism intersects with the old Enlightenment and post-Enlightenment dichotomy of civilized–barbarians and how it is reconfigured to construct those incapable of fitting within the entrepreneurial spirit of the free market efficiency as unwilling to democratize. The case of Bulgarian, predominantly Roma, schools serves to illustrate how peoples who are Othered in the western European discourse designate their own Other, and thus provides a fruitful approach to understanding how Roma's social exclusion is constructed and situated.